2015
DOI: 10.1080/10942912.2014.966388
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antioxidant Properties ofAchillea Millefoliumfrom the Eastern Region of Iran

Abstract: The aim of present study was to evaluation the antioxidant potential of Achillea millefolium on the basis of the chemical compositions of oils obtained by hydrodistillation. In the case of Achillea millefolium, twenty-four compounds were identified representing the 83.76% of the total oil. The major constituents of the oil were described as α-pinene (10.12%), camphene (4.23%), limonene (5%), borneol (5%), γ-terpinene (8%), carvone (5%), bornyl acetate (2.43%), thymol (15.32%), and carvacrol (20.43%). The oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Cis‐chrysanthenol (Judzentiene, ), α‐pinene, β‐pinene and β‐phellandrene (Sevindik et al, ; Kazemi, ; Costescu et al ., ; Falconieri et al, ; Nadim et al ., ; Conti et al, ; Bimbiraite et al, ; Anne et al ., & ; Nemeth, ; Boskovic et al, ; Rohloff et al, ; Hofmann et al, ), p‐cymene (Ebadollahi et al, ; Yousefzadeh and Zeinivand, ; Nadim et al ., ; Anne et al ., ; Jaimand et al, ), α‐thujane, α‐terpinene and γ‐terpinene (Mazandarani et al, ), camphene and limonene (Kazemi, ; Nadim et al ., ; Bimbiraite et al, ) and sabinene (Nadim et al ., ; Conti et al, ; Boskovic et al, ) are the hydrocarbon monoterpenes identified in A. millefolium .…”
Section: Chemical Constituents Of a Millefoliummentioning
confidence: 99%
See 2 more Smart Citations
“…Cis‐chrysanthenol (Judzentiene, ), α‐pinene, β‐pinene and β‐phellandrene (Sevindik et al, ; Kazemi, ; Costescu et al ., ; Falconieri et al, ; Nadim et al ., ; Conti et al, ; Bimbiraite et al, ; Anne et al ., & ; Nemeth, ; Boskovic et al, ; Rohloff et al, ; Hofmann et al, ), p‐cymene (Ebadollahi et al, ; Yousefzadeh and Zeinivand, ; Nadim et al ., ; Anne et al ., ; Jaimand et al, ), α‐thujane, α‐terpinene and γ‐terpinene (Mazandarani et al, ), camphene and limonene (Kazemi, ; Nadim et al ., ; Bimbiraite et al, ) and sabinene (Nadim et al ., ; Conti et al, ; Boskovic et al, ) are the hydrocarbon monoterpenes identified in A. millefolium .…”
Section: Chemical Constituents Of a Millefoliummentioning
confidence: 99%
“…Oxygenated monoterpenes including camphor, borneol and bornyl acetate (Sevindik et al, ; Ebadollahi et al, ; Kazemi, ; Mazandarani et al, ; Conti et al, ; Rahimmalek et al, ; Boskovic et al, ; Candan et al, ), piperitone (Ebadollahi et al, ), carvacrol and carvone (Kazemi, ), 1, 8‐cineole (Sevindik et al, ; Yousefzadeh and Zeinivand, ; Nadim et al ., ; Judzentiene and Mockute, ; Conti et al, ; Rahimmalek et al, ; Anne et al ., ; Candan et al, ; Bezic et al, ), α‐terpineol and terpinen‐4‐ol (Sevindik et al, ; Nadim et al ., ; Candan et al, ), artemisia ketone (Mazandarani et al, ; Conti et al, ), α‐thujone, β‐thujone, linalool and fenchyl acetate (Mazandarani et al, ; Anne et al ., ), dihydrocarveol and chrysanthenyle acetate (Yousefzadeh and Zeinivand, ), trans‐thujone and trans‐crhysanthenyl acetate (Falconieri et al, ) and myrecene (Bezic et al, ) were isolated from A. millefolium .…”
Section: Chemical Constituents Of a Millefoliummentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant activity of the plant was measured by DPPH free radical scavenging method as described. [11,12] In the assay, 0.1 mM solution of DPPH was prepared in ethanol and 0.5 mL of this solution was added to 1.5 mL of extract solution in ethanol at different concentrations (20-100 μg/ mL). These solutions were vortexed in depth and incubated in the dark at 25°C for 30 min.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…[6] Species of the genus Achillea are widely used for numerous pharmacological properties, such as antimicrobial, anti-inflammatory, antiallergic, and antioxidant activities. [3,7,8] Also in Iran, Achillea species are used as diuretic and menstrual regularity agents for wound healing, diarrhea, flatulence, and abdominal pain. [9,10] Phenolic compounds, such as flavonoids and phenolcarbonic acids, constitute one of the most important groups of pharmacologically active components in yarrow.…”
Section: Introductionmentioning
confidence: 99%